Gambaran Pengetahuan, Sikap, dan Perilaku Sopan Santun Mahasiswa Baru Prodi Kebidanan Program Sarjana, Fakultas Kesehatan, Universitas Ngudi Waluyo Tahun 2022 - Wahyu Kristiningrum; Moneca Diah Listiyaningsih; Risma Aliviani Putri (Indonesian Journal of Midwifery (IJM), 2022)
Introduction: Polite. Courtesy is a desirable trait and a fair value. The term "politeness" refers to the attitude or behavior of individuals who respect other people and are friendly in communicating with people who are interacting with them. (Djuwita, 2017). Respect for others can be shown through one's words, deeds, or actions. Lately, many teenagers who behave politely at school have started to disappear. Like when a teenager talks to a teacher, he doesn't use polite language and treats the teacher like a friend. Often we hear someone swearing and saying dirty words in the family, neighborhood, and local area, and sometimes even in the educational environment. This impolite attitude and behavior are usually in uenced by friends, neighbors, and people who are older than students, as well as by families or environments that are used to using foul language. It is even in uenced by unscrupulous persons who can be provoked through social media, such as television dramas or serial lms on YouTube, Facebook, Instagram, and other platforms. Politeness is an attitude or behavior that is orderly and follows customs or norms. It is a daily gesture of mutual respect, kindness, humility, and a willingness to help others. Manners are part of ethical terminology, which is always associated with moral terminology or moral philosophy. From two Greek words, the word ethics comes from its etymology: ethos as well as ethos The term "ethos" refers to nature, "customs". character," and "ordinary location." Etichos refers to conduct, good deeds, decency, and morality. Mores, meaning "is," is the Latin word for morals. Lately, many teenagers have lost manners in the school environment. For example, a teenager speaks the polite language to a teacher and considers a teacher like a friend so that he is free to speak without using polite language. (Kompasiana.com, 2022). This impolite attitude and behavior are usually in uenced by the family or environment that used to say dirty or obscene words, the in uence of friends, neighbors, and people who are older than students. Even the in uence of immoral people who provoke them through social media such as drama/ lm series on television, youtube, Facebook, Instagram, WhatsApp, and so on. This research uses a quantitative descriptive research design, namely to describe the characteristics of the population or phenomenon being studied. The population in this study were all new students of the undergraduate midwifery study program with a total of 29 respondents. Research Sample: Sampling using total sampling with a total sample of 29 respondents. The method of collecting data is using a questionnaire that has been adopted in the form of a statement. Time to ll out the questionnaire on August 26, 2022. The data analysis used in this study was univariate analysis which aimed to nd out the description, knowledge, attitudes, and polite behavior of new students of the midwifery study program, Faculty of Health, Ngudi Waluyo University. The results of the courtesy study for new students of the Midwifery Study Program Undergraduate Program, Faculty of Health, Ngudi Waluyo University, namely good knowledge with a positive attitude of 93.3%, good knowledge with a negative attitude of 6.7%. Good knowledge with positive behavior of 86.67%, good knowledge with negative behavior of 13.33%. The study obtained an overview of the conclusion that the manners of new students are mostly in the category of good knowledge and have positive attitudes and behavior. although there is still a lack of knowledge and negative attitudes and behaviors, this is a joint effort to build each other up so that when you become a midwife, good attitudes and behaviors are formed for all students. The development of the times and technology, especially digital can affect students' polite behavior. For this reason, research still needs to be carried out on the in uence of the times and digital technology on student politeness.Abstrak Sopan santun adalah sifat yang disukai dan nilai yang wajar. Istilah â€œkesopananâ€ mengacu pada sikap atau perilaku individu yang menghormati orang lain dan ramah dalam berkomunikasi kepada orang yang sedang berinteraksi dengannya. (Djuwita, 2017). Menghargai dan memahami orang lain dapat ditunjukkan melalui ucapan, perbuatan, atau tindakan seseorang. Belakangan ini banyak remaja yang berperilaku sopan santun di kampus sudah mulai menghilang. Seperti ketika seseorang mahasiswa berbicara dengan seorang dosen, dia tidak menggunakan bahasa yang sopan dan memperlakukan dosen seperti seorang temannya. Sering kita mendengar seseorang mengumpat dan mengatakan perkataan kotor di lingkungan keluarga, tetangga dan daerah setempat, dan kadang-kadang bahkan dalam lingkungan pendidikan. Sikap dan perilaku tidak sopan ini biasanya dipengaruhi oleh teman, tetangga, dan orang yang lebih dewasa dari mahasiswa, juga seperti oleh keluarga atau lingkungan yang terbiasa menggunakan bahasa kotor. Bahkan dipengaruhi oleh oknum yang tidak bermoral yang dapat memprovokasi melalui media sosial, seperti drama televisi atau film serial di YouTube, Facebook, Instagram, dan platform lainnya. Kesopanan adalah sikap atau perilaku yang tertib dan sesuai dengan adat atau norma. Itu adalah sikap sehari-hari untuk saling menghormati, kebaikan, kerendahan hati, dan kesediaan untuk membantu orang lain. Sopan santun ialah istilah bagian dari terminologi etika, yang selalu dapat dikaitkan dengan istilah terminologi moral atau filsafat moral. Dari dua kata Yunani, kata etika berasal dari etimologinya: etos dan juga ethikos Istilah "ethos" mengacu pada alam, "kebiasaan". karakter," dan "lokasi biasa." Etikhos mengacu pada perilaku, perbuatan baik, kesopanan, dan moralitas. Mores, yang berarti "adalah," adalah kata Latin untuk moral. Akhir-akhir ini banyak seorang remaja yang sikap sopan santun dilingkungan kampus hilang. Contoh seorang remaja. berbicara dengan seorang dosen. tidak menggunakan bahasa yang sopan dan menganggap seorang dosen tersebut seperti temannya sendiri sehingga mereka beba berbicara tanpa menggunakan bahasa yang sopan.(Kompasiana.com, 2022). Perbuatan sikap dan perilaku yang tidak sopan ini, seringnya dipengaruhi oleh keluarga atau lingkungan yang terbiasa berkata kotor atau jelek, pengaruh teman, tetangga, orang-orang yang lebih tua dari mahasiswa. Bahkan pengaruh dari orang-orang tidak berakhlak yang memprovokasi. Lewat media sosial seperti drama/ film cerita bersambung di televisi, youtube, facebook, instagram, whats'up dan lain sebagainya. dalam pelaksanaan penelitian ini menggunakan desain penelitian deskriptif kuantitatif yaitu untuk menggambarkan karakteristik populasi atau fenomena yang sedang diteliti. Populasi dalam penelitian ini adalah seluruh mahasiswa baru prodi kebidanan program sarjana sejumlah 29 responden. Sampling menggunakan total sampling dengan jumlah sampel sebanyak 29 responden. Metode pengumpulan data adalah menggunakan kuesioner yang telah diadopsi berupa pernyataan. Waktu pengisian kuesioner pada tanggal 26 Agustus 2022. Analisis data yang digunakan dalam.penelitian ini adalah analisis univariat yang bertujuan untuk mengetahui gambaran pengetahuan, sikap, dan perilaku sopan santun mahasiswa baru Prodi Kebidanan Program Sarjana, Fakultas Kesehatan, Universitas Ngudi Waluyo.